DIGITAL MARKETING FOR HALAL FOOD PRODUCT: THE EFFECT OF CUSTOMER REVIEW, HALAL CONTENT, AND USE OF E-PAYMENT - Arsiati, Rira; Eri Puspita, Rosana (Journal of Islamic enterpreneurship and Management, 2023)
This research examines the influence of customer reviews, halal content marketing, and the use of e-payment on consumer loyalty with purchasing decisions as an intervening variable at Mie Gacoan. The data used in this research is primary data, using a questionnaire. The questionnaire was distributed to 100 respondents, with the criteria being Muslim generation Z respondents (11-26 years old). The sampling technique used was KMO (Kaiser Mayer Olkin). The analysis techniques used in this research are validity test, reliability test, partial test (t test), simultaneous test (f test), coefficient of determination test, normality test, multicollinearity test, heteroscedasticity test, and Sobel test. The object of this research is Mie Gacoan. The results of this research show that the variables customer reviews, halal content marketing, and the use of e-payment have a positive and significant effect on purchasing decisions. Customer reviews, halal content marketing, and the use of e-payment have a positive and significant effect on consumer loyalty. In the Sobel test, the purchasing decision variable could mediate the influence of customer reviews, halal content marketing, and the use of e-payment on consumer loyalty.